2022
DOI: 10.3390/cancers14215350
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Fusobacterium nucleatum in Colorectal Cancer Cell Proliferation and Migration

Abstract: Colorectal cancer (CRC) is a common cancer worldwide with poor prognosis. The presence of Fusobacterium nucleatum (Fn) in the intestinal mucosa is associated with the progression of CRC. In this review, we explore the mechanisms by which Fn contributes to proliferation and migration of CRC cells from the following four aspects: induction of the epithelial–mesenchymal transition (EMT), regulation of the tumor microenvironment (TME), expression of oncogenic noncoding RNAs, and DNA damage. This review outlines th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 87 publications
(128 reference statements)
0
4
0
Order By: Relevance
“…This cascade, in turn, engenders tumor cell proliferation and migration. 28 , 76 Furthermore, Gram-negative bacteria, including F. nucleatum , release outer membrane vesicles (OMVs), extracellular vesicles containing cytoplasmic and periplasmic components enclosed within a protein-lipid bilayer. 77 F. nucleatum has been substantiated as an activator of TLR4 through the discharge of OMVs, instigating a sequence that involves NF-κB, CREB, extracellular signal-regulated kinases, and inflammatory cytokines within human cell lines and colon-like monolayers.…”
Section: F Nucleatum and Tumorigenesis Tumor Metastasismentioning
confidence: 99%
“…This cascade, in turn, engenders tumor cell proliferation and migration. 28 , 76 Furthermore, Gram-negative bacteria, including F. nucleatum , release outer membrane vesicles (OMVs), extracellular vesicles containing cytoplasmic and periplasmic components enclosed within a protein-lipid bilayer. 77 F. nucleatum has been substantiated as an activator of TLR4 through the discharge of OMVs, instigating a sequence that involves NF-κB, CREB, extracellular signal-regulated kinases, and inflammatory cytokines within human cell lines and colon-like monolayers.…”
Section: F Nucleatum and Tumorigenesis Tumor Metastasismentioning
confidence: 99%
“…Notably, an increased presence of Fusobacterium nucleatum in CRC patients compared to healthy individuals has emerged as a significant marker for CRC diagnosis (5). Studies have shown that F. nucleatum promotes CRC progression by activating signaling pathways such as Ecadherin/β-catenin and TLR4/MyD88, and modulating autophagy and immune responses (6). Moreover, F. nucleatum is implicated in various molecular events, including microsatellite instability (MSI), CpG island methylator phenotype (CIMP), and tumorigenic mutations in genes such as TP53, BRAF, CHD7, and CHD8, Jundishapur J Microbiol.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have shown an increase in Fusobacterium species in patients with CRC compared with healthy individuals and inflammatory tissue of the colon in the precancerous phase [ 11 , 12 ]. Fusobacterium nucleatum ( F. nucleatum ) is an anaerobic gram-negative bacterium that uses its pathogenic factors, such as adhesion molecules and lipopolysaccharide, to induce inflammation and activate the immune system's immune responses through various cellular signaling pathways [ 13 , 14 ]. According to the results of studies on the early detection and diagnosis of CRC, various genetic factors can be used as molecular markers for the early detection of CRC, including the family of miRNAs [ 15 ].…”
Section: Introductionmentioning
confidence: 99%